The Effectiveness of Collaborative E-Learning Model in Reducing High School Students' Misconceptions on Heat: Efektivitas Penggunaan Model Pembelajaran Kolaboratif Berbasis E-Learning Dalam Mereduksi Miskonsepsi Kalor Pada Siswa SMA - Haryono, Heny Ekawati; Al Mubarokah, Nurul Hidayah; Prihatiningtyas, Suci; Zayyadi, Moh; Kaniawati, Ida; Marzuqi, Iib (SEJ (Science Education Journal), 2024)
This study aimed to determine the reduction in high school students' misconceptions on heat after applying a collaborative e-learning-based learning model. The research design is an experimental study using a one-group pre-test and post-test design. The data collection technique is quantitative, conducted through written tests (pre-test and post-test) given to both classes. The written test is accompanied by a confidence scale (0-5). If a student's answer (S) and confidence scale are high, then the student is classified as experiencing a misconception. The pre-test serves as the initial identification of student misconceptions, while the post-test serves as the final identification of student misconceptions. Then the data is represented in a bar diagram. After obtaining quantitative data, it is then analyzed descriptively. The research findings shows that the reduction in misconceptions for Class A was 12.50%, and was 13.33% for Class B. The existence of students identified as having resistant misconceptions contributes to an average percentage of misunderstanding reduction below 50%. However, implementing the collaborative e-learning-based learning model has shown to be effective in reducing misconceptions. The resistant misconceptions occurred due to the students' learning styles or the time required for students to construct concepts taking a considerable amount of time.